Random amplified polymorphic DNA PCR in the teaching of molecular epidemiology - Reinoso, Elina Beatríz (2016)
In this article, we describe a basic practical laboratory designed for fifth-year undergraduate students of Microbiology as part of the Epidemiology course. This practice provides the students with the tools for molecular epidemiological analysis of pathogenic microorganisms using a rapid and simple PCR technique. The aim of this work was to assay RAPD-PCR technique in order to infer possible epidemiological relationships. The activity gives students an appreciation of the value of applying a simple molecular biological method as RAPD-PCR to a discipline-specific question. It comprises a three-session laboratory module to genetically assay DNAs from strains isolated from a food outbreak.